Characteristics and Patterns of Urbanization of Non-Urban Regions: the case of Kudus Regency in Central Java Province, Indonesia - Sari, Retno Tunjung; Mardiansjah, Fadjar Hari (Journal of Regional and City Planning, 2025)
Urbanization in Java is characterized by processes that occur outside the boundaries of cities, particularly in the territories of regencies that are still perceived as non-urban districts. Using the case of Kudus Regency in Central Java Province, this study analyzed the urbanization process that takes place in Javanese regencies, highlighting the importance of the process outside of cities, especially in regencies with high urbanization levels. The analysis showed that the urbanization process is reflected in the spatial expansion of urbanized villages and the growing urban population in growing urban areas in the regency. The pattern and characteristics of urbanization in Kudus Regency are relatively independent from the influence of major cities that are located more than 60 km away, and the process has been observed as accommodating the growing population and its activities in growing urban areas. The spatial growth in the urbanization process corresponds with the growth in population density, supported by the availability of three spatial elements: a high-density core, lesser-density areas close to the core, and road networks connecting them. The analysis further showed that the urbanization process that takes place in Kudus Regency is an in-situ urbanization process in the capital that leads to the formation of a larger city, with the economic and demographic factors of the region supporting and determining the speed and direction of the process. The fast rate of the urbanization process and the expansion of urban areas in the regency are challenging, necessitating management in the same manners as in cities.